Odpowiedzi

  • Użytkownik Zadane
2009-11-13T14:20:14+01:00

a) ( x + 4 ) + ( 2x - 6 ) = 3x -2
b) -( 2y + 3x ) + ( - 4y + 2x + 1 )= -2y -3x -4y +2x +1= -6y-5x+1
c) -(x - 2xy ) - ( 4x + xy ) + ( xy - x )=-x+2xy-4x-xy+xy-x=-6x+2xy
d) ( x² + 2x + 1 ) - ( x² - 4x + 3 )= x kawdrat +2x +1 - x kwadrat +4x-3=6x-2


Mam nadzieję że pomoglem :D
2009-11-13T14:21:58+01:00
X+4+2x-6=3x-2
-2y-3x-4y+2x+1=-x-6y+1
-x+2xy-4x-xy+xy-x=-2x+2xy
x²+2x+1-x²-4x+3=-2x+4
2009-11-13T14:22:07+01:00
A) ( x + 4 ) + ( 2x - 6 ) = x + 4 + 2x - 6 = 3x - 2
b) -( 2y + 3x ) + ( - 4y + 2x + 1 ) = - 2y - 3x -4y + 2x + 1 =
- x - 6y + 1
c) -(x - 2xy ) - ( 4x + xy ) + ( xy - x ) = - x + 2xy -4x - xy + xy - x =
- 6x + 2xy
d) ( x² + 2x + 1 ) - ( x² - 4x + 3 ) = x² + 2x + 1 - x² + 4x - 3 =
6x -2

Myślę, że pomogłam ;)